They are Preschoolers, not Scholars! - Kumar, Amruth G. (THE PRIMARY TEACHER, 2022)
The formative or preschool period is the most essential period to develop social, emotional and physical competencies. In recent years, with the development of a large number of preschools, the quantitative element might be met, but we are far off from the qualitative leap. School readiness is the most crucial aspect to preventing the increasing number of dropouts. While government initiatives are well in place, their implementation at the grassroot level has significantly failed reflecting a steep decline in the Gross Enrolment Ratio (GER) while moving from the lower classes to the upper classes. This paper discusses the significant and often overlooked issues while considering pre-primary and primary education. It is also an effort towards identifying the problem areas and proposing a better approach towards imparting knowledge and enhancing learning outcomes. The paper concludes with a reflection on the need for trained teachers and better administration as the most important elements of a sustainable society